2004
DOI: 10.1291/hypres.27.319
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Attrition in White Blood Cell Correlating with Cardiovascular Damage

Abstract: Aging is a major risk factor for cardiovascular disease. Chronological aging does not always parallel biological aging, but there is no reliable biomarker for the latter. In the present study, we tested the hypothesis that telomere attrition in white blood cells is related to endothelial dysfunction and the extent of atherosclerosis, and thus may serve as a useful marker for biological aging. We evaluated telomere lengths in white

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…Interestingly, exogenous NO reduced human umbilical vein endothelial cell senescence and delayed age-dependent inhibition of telomerase activity, suggesting that telomerase inactivation precedes endothelial cell senescence and that NO prevents age-related downregulation of telomerase activity and delays endothelial cell senescence. 132 Nakashima et al 133 showed by measuring the mean telomere restriction fragment length that telomere lengths in white blood cells shorten in parallel to a decline in endothelial function by FMD in patients with various degrees of cardiovascular damage as well as in healthy subjects.…”
Section: Endothelial Cell Senescencementioning
confidence: 99%
“…Interestingly, exogenous NO reduced human umbilical vein endothelial cell senescence and delayed age-dependent inhibition of telomerase activity, suggesting that telomerase inactivation precedes endothelial cell senescence and that NO prevents age-related downregulation of telomerase activity and delays endothelial cell senescence. 132 Nakashima et al 133 showed by measuring the mean telomere restriction fragment length that telomere lengths in white blood cells shorten in parallel to a decline in endothelial function by FMD in patients with various degrees of cardiovascular damage as well as in healthy subjects.…”
Section: Endothelial Cell Senescencementioning
confidence: 99%
“…2 The telomere length in white blood cells (WBCs) reflects the cumulative burden of oxidative stress and inflammation in the circulation during an individual's lifetime 3 and has been reported to be a useful marker of biological aging of the cardiovascular system. 4,5 Telomere length has been observed to decrease with increases in cardiovascular risk factors such as hypertension, hyperlipidemia, diabetes, obesity and cigarette smoking. 6 We recently showed that the shortening of the telomeres in peripheral leukocytes was accelerated with advancing age 7 and it was also observed in patients with sarcoidosis 8 and Parkinson's disease 9 in the Japanese population.…”
mentioning
confidence: 99%
“…Although we did not study telomeres length in vascular cells, it has been demonstrated that circulating blood leucocyte DNA content is predictive of vascular telomere content and also is an accurate surrogate for vascular aging in population studies (Nakashima et al 2004;Wilson et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…They consist of several thousands of repetitive sequences of TTAGGG that are naturally shortened with each cell division due to the end replication problem (Nakashima et al 2004;Saliques et al 2010). Progressive attrition of telomeres leads to a critical length that triggers the cell arrest phenomenon known as senescence (Khan et al 2012), and due to the universal fact that telomere shorten with age, its study is crucial for understanding mechanisms of age-related diseases (Armanios 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation